The Taxation Implicit in Two-Tiered Exchange Rate Systems - Huizinga, Harry (IMF Working Papers; Working Paper ;, 1996)
A two-tiered exchange rate system can be interpreted as a set of separate taxes on money and other financial assets. If the official two-tiered exchange rate system coexists with a black market for foreign exchange, then there is implicit taxation of the international goods trade as well. This paper presents some evidence on the tax rates and tax revenues implicit in the exchange rate systems of The Bahamas (from 1978 to 1995), the Dominican Republic (from 1970 to 1984), and South Africa (from 1973 to 1995).